Use and abuse of synthetic progestins - Blanchard, Oscar (2015)
Progestábenos called progestin or synthetic or artificial progestins (hydroxyprogesterone caproate 17, ethyl 6-methyl-hydroxyprogesterone 17) and cause nortestosteronas in mammals, and other progestational reaction, favor nidation and pregnancy. These progestins are obviously of the latest developments in the endrocrinología to the point that their study is not yet a finished and ongoing review question. It has been found that this action is not identical -empíricamente- although much more active than progesterone or progestin; it has no androgenic effects and acts only by injection. Really we do not have a thorough knowledge about the North-synthetic steroids; Steroids are a cyclopentane fenartreno chemical structure.